Witamina K w cholestazie w świetle aktualnych wytycznych - opis przypadku - Lipiński, Patryk; Pleskaczyńska, Agata; Jankowska, Irena; Dobrzańska, Anna (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Vitamin K deficiency bleeding (VKDB) is a rare and potentially life-threatening disorder. Infants suffering from cholestasis constitute a risk group of vitamin K deficiency due to intestinal malabsorption defects. The paper presents a case of late-onset VKDB as a result of biliary atresia in an infant.